2007
DOI: 10.1055/s-2007-970686
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Abuse in Childhood and Youth as Psychopathologically Relevant Life Occurrence: Cross-sectional Survey

Abstract: Aim. To assess the perpetrators of sexual abuse in childhood, forms of simultaneous abuse, and characteristics of the families of origin, and the possible effects of abuse on health in adult life. Methods. A cross sectional study conducted between 1998 and 2002 included a random group of 936 inpatients (723 women) aged (mean±standard deviation) 41.0±2.5 years at the psychosomatic clinic in Simbach, Germany. The following questionnaires, previously validated in German, were used to assess the patients:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
3
16
0
2
Order By: Relevance
“…Among the patients admitted to the center for treatment, 41.8% were diagnosed with post-traumatic stress disorder, while 41.8% were diagnosed with conduct disorders, 6.9% with depression, 2.8% with attention deficit hyperactivity disorder and 2.8% with acute stress disorder. According to previous studies, children who are victims of sexual abuse are often diagnosed with conditions such as post-traumatic stress disorder, conduct disorder, attention deficit hyperactivity disorder, oppositional defiant disorder, dissociation and impulse control disorder (38)(39)(40), and in our study also, it was observed that abuse and neglect victims were given similar diagnoses according to the DSM-IV.…”
Section: Discussionsupporting
confidence: 70%
“…Among the patients admitted to the center for treatment, 41.8% were diagnosed with post-traumatic stress disorder, while 41.8% were diagnosed with conduct disorders, 6.9% with depression, 2.8% with attention deficit hyperactivity disorder and 2.8% with acute stress disorder. According to previous studies, children who are victims of sexual abuse are often diagnosed with conditions such as post-traumatic stress disorder, conduct disorder, attention deficit hyperactivity disorder, oppositional defiant disorder, dissociation and impulse control disorder (38)(39)(40), and in our study also, it was observed that abuse and neglect victims were given similar diagnoses according to the DSM-IV.…”
Section: Discussionsupporting
confidence: 70%
“…For instance, there is evidence that traumatic experience may result in degradation of specific brain regions involved in learning, memory, and emotion (Bremner, 1999;Bremner & Vermetten, 2001). Although early traumatic stress (Nickel et al, 2004) and neuropsychological deficits (Ruocco, in press) are well-documented features of BPD, the potential causal linkages between these factors and psychopathology are as yet unknown (see Jelicic & Merckelbach, 2004). On the basis of the current evidence, however, it appears that BPD is indeed characterized by clear biological abnormalities with potential interactions between biological systems and psychosocial stressors resulting in BPD psychopathology, thus refuting at least in part those arguments for a distinction between Axis I and Axis II conditions based solely on biological causal differences between these two classes of disorders.…”
Section: Functional Neuroimaging Findingsmentioning
confidence: 99%
“…The focus on difficulty forming and maintaining relationships is echoed further in Linehan's (1993) proposition that BPD develops when people with a dispositional vulnerability in terms of difficulty controlling their emotions are raised in a family that is invalidating, where emotions are discounted and disrespected. The relational theme is also to be found in Fonagy et al (1996) where they observe that those classified as having a "preoccupied/ enmeshed" attachment style are more likely to have a BPD diagnosis than those with standard attachment and likewise in the work of Nickel et al (2004) who found that those sexually abused during childhood (a precursor of nonstandard attachment) are significantly more likely to develop BPD as adults than those who were not. Similarly, the interpersonal narrative appears in Hill, Fudge, Harrington, Pickles, and Rutter (2000), who compared personality assessment methods and conclude that PD may be assessed in terms of interpersonal and social role performance because " .…”
Section: Discussionmentioning
confidence: 62%